The impact of secular education on the Muslim youth in Singapore : challenges and remedies in the 21st Century - Farah Zidah Jelani (International Institute of Islamic Thought and Civilisation, International Islamic University Malaysia,1, 2021)
The purpose of this study is to create an awareness in the Muslim society that practicing Islam must be a top priority in their daily lives. The study aims to highlight the importance of making Islam a priority in the daily activities of a Muslim life despite being in a secular environment. This researcher does this by identifying the problems Muslims face in a secular state to solve them. Thereby making it easier for Muslims to practice the deen/religion. The researcher identifies the impact of secularism on the mindset of Muslim youth in Singapore. To explore solutions that can be implemented in the future by Muslims in Singapore. The study will aim for a three-pronged approach at parents, youth themselves and all Muslim organization, raising awareness and for them to take action. The methodology employed in this study is qualitative research design. The researcher focuses on the primary and secondary sources to gather information in answering the questions as research objectives such as review of the related journals, the printed and un-printed books. The questionnaire would also be distributed online and make it viral, to gain a fast and effective result. The results of the findings will be discussed and analyzed toward the end of this research paper. Thus, this study objective to bring out the awareness needed for the parents and the Muslim youth to take an introspective look towards their goal in life and make changes to their lives following Islamic lifestyles. From the conducted survey, the results led to a huge majority in agreement to the research problem and criminal acts by Muslims are due to the failure in overcoming challenges with the approach of the teachings of Islam. The results indicate that the Muslim identity has not lost but needs further refinement for the light of Islam to shine out. Thus, the researcher decided that to carry-on what have been established by MUIS, PERGAS and all other NGO’s (regarding Islamic education) and propose a “National Campaign” to run simultaneously at all levels.